Anti-müllerian Hormone During Natural Cycle Presents Significant Intra and Intercycle Variations When Measured With Fully Automated Assay - Melado, Laura; Lawrenz, Barbara; Sibal, Junard; Abu, Emmanuel; Coughlan, Carol; Navarro, Alfredo T.; Fatemi, Human Mousavi (Frontiers in Endocrinology, 2018)
Anti-Müllerian hormone (AMH) is an important ovarian reserve marker for baseline assessment and therapeutic strategy in fertility treatments, which is considered reliable when measured on any day of the cycle. Recent data have pointed towards significant fluctuations of AMH and questioned whether a single measurement is reliable for clinical decision-making. The aim of this study was to evaluate whether the AMH does have significant variations during a natural cycle when a fully automated assay is used for the sample analysis. We performed a prospective study including healthy volunteers with regular cycles, from April to December 2017. Blood samples for AMH, FSH, LH, estradiol and progesterone were obtained on day 2/3, day 10, day of LH surge, luteal phase and day 2/3 of subsequent menses. AMH analysis was performed with Elecsys® AMH automated assay. Trial was registered with clinical.trials.gov: NCT03106272. One hundred samples from 22 women with a mean age of 30.7±4.11 years and a BMI of 23.2±3.63 kg/m² were analysed. There was a substantial longitudinal fluctuation in AMH levels, indicated by the coefficient of variation (CV) intra-cycle of 0.207±0.143. A positive correlation between LH and AMH concentrations was found at the moment of LH rise (p<0.0001). Absolute intra-individual inter-cyclic variability was 0.75 ng/mL (range: 0.03–2.81ng/mL) and inter-cycle CV was 0.28 (Confidence interval: 0.16-0.39; p<0.0001). According to our results, with the use of a fully automated assay in natural cycle, AMH shows significant intra- and inter-cycle variations, which are not caused by analytical variability. Future investigations, evaluating AMH dynamics and the best time for AMH assessment should be conducted.